A picture of pioneer times in California, illustrated with anecdotes and stories taken from real life. - White, William Francis, 1829-1891? (San Francisco, Printed by W.M. Hinton & co., 1881)
William Francis White (1829-1891?) and his young wife sailed from New York in 1849 round the Horn to San Francisco, where he set up an import business. He later represented Santa Cruz in the state constitutional convention and served as a bank commissioner. A picture of pioneer times in California (1881), written under the pseudonym "William Grey," presents White's revisionist version of California history challenging the picture presented in the 1854 Annals of San Francisco. In particular, he attacks the Annals' discussion of the Mission Fathers and the Mission Indians, the United States conquest of California in the Mexican War, discovery of gold at Sutter's Fort, and the role of women during the Gold Rush. He also reminisces about his voyage to California and experiences as a San Francisco merchant, 1849-1850, as well as legends of the gold mines. The volume concludes with three fictional tales of California in the Gold Rush.
Includes three tales, illustrative of life in California: Ellen Harvey; or The wife's disappointment (p. [213]-291); Ada Allen; or, The husband's surprise (p. [293]-399); Minnie Wagner; or, The forged note (p. [401]-677).
Also available in digital form on the Library of Congress Web site.
Keywords: Frontier and pioneer life -- California; California -- Gold discoveries; Ethnic groups -- California; Women -- California; Urbanization -- California; Real estate development -- California; Law -- Political aspects -- California; Business -- California